Fabrication of a trans-scale bimetallic synergistic enhanced Raman scattering substrate with high surface-enhanced Raman scattering activity. Issue 5 (18th February 2015) - Xie, Wanyi; He, Shixuan; Xia, Liangping; Zhang, Hua; Zhang, Wei; Shen, Zexiang; Liu, Xiaohong; Hu, Jianming
Abstract : A novel trans-scale bimetallic synergistic enhanced Raman scattering (TBSERS) substrate was fabricated and employed for sensitive detection of bisphenol A (BPA). Abstract : A novel enhanced Raman scattering substrate was fabricated using a vacuum-deposited Ag island film on Au film inverted pyramid pits (period is 2 μm). This trans-scale bimetallic synergistic enhanced Raman scattering (TBSERS) substrate was optimized for the detection of bisphenol A, and the detection limit can be as low as 0.5 ppm by this method.